The Influence of Brand Image Service Quality and Green Marketing on Consumer Purchasing Decisions of The Body Shop at Malls in South Jakarta - Rasyid, Amanda Rachmawati; Hardini, Resti; Digdowiseiso, Kumba (Equivalent: Jurnal Ilmiah Sosial Teknik, 2024)
This study aims to analyze the effect of service quality, brand image, and green marketing on consumer purchasing decision of The Body Shop at mall in South Jakarta. The result of this research is using primary data in the form of questionnaires to 100 respondents of The Body Shop consumers in mall in South Jakarta using Statistical Product and Service Solutions (SPSS) method. Data collection techniques in this study by observation and survey, unstructured interviews, and using questionnaires. The result of the research using F test and t test indicate that there is influence of service quality, brand image and green marketing towards purchasing decision of The Body Shop at mall in South Jakarta.